2016
DOI: 10.1016/j.meegid.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

ABO, Secretor and Lewis histo-blood group systems influence the digestive form of Chagas disease

Abstract: Chagas disease, caused by Trypanosoma cruzi, can affect the heart, esophagus and colon. The reasons that some patients develop different clinical forms or remain asymptomatic are unclear. It is believed that tissue immunogenetic markers influence the tropism of T. cruzi for different organs. ABO, Secretor and Lewis histo-blood group systems express a variety of tissue carbohydrate antigens that influence the susceptibility or resistance to diseases. This study aimed to examine the association of ABO, secretor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…A study in a semi-isolated Black community in Northern Brazil reported a very similar SeLe phenotypes (from saliva and blood samples) distribution to Burkina Faso [53]. A study conducted in the state of São Paulo, Brazil [54] with 827 participants regardless of ethnicity revealed a prevalence of Se+Le+ phenotype (from blood samples) in 78% of the population, similarly with the Se+Le+ prevalence in our cohort (76%; from human milk samples), which was also composed by different ethnicities. Our cohort presented a SeLe distribution closer to the Caucasian/Asian than the semi-isolated Black from Northern Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…A study in a semi-isolated Black community in Northern Brazil reported a very similar SeLe phenotypes (from saliva and blood samples) distribution to Burkina Faso [53]. A study conducted in the state of São Paulo, Brazil [54] with 827 participants regardless of ethnicity revealed a prevalence of Se+Le+ phenotype (from blood samples) in 78% of the population, similarly with the Se+Le+ prevalence in our cohort (76%; from human milk samples), which was also composed by different ethnicities. Our cohort presented a SeLe distribution closer to the Caucasian/Asian than the semi-isolated Black from Northern Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Although the frequency of the secretor phenotype varies across populations, approximately 80% of the world population are secretors [ 16 ]. In Brazil, the prevalence of this phenotype revealed in the few studies, is somewhat similar, ranging from 75% to 90% [ 28 , 49 , 50 , 51 ]. The 82% of secretors in the control group found in the present study were therefore consistent with these previous observations.…”
Section: Discussionmentioning
confidence: 98%
“…[ 105 ]. In Brazil, the variants IL17A and IL17F are associated with the development of cardiomyopathy [ 106 ] In the African/African-American population, p.Arg514-Gly, a polymorphism of ACE2, is associated with cardiovascular and pulmonary conditions [ 107 ] In Genome-wide Association Study (GWAS) in Italian and Spanish hospitals, a 3p21.31 gene cluster encompassed the SLC6A20, LZTFL1, CCR9, FYCO1, CXCR6, and XCR1 genes [ 108 ] Genetic polymorphisms of Interferon-γ Production In the Brazilian population, genotypes and alleles of IL12B and IL-10 could be associated with a failure to regulate Th1 responses, IFNγ production, and an increased risk of chronic CD cardiomyopathy [ 109 ] Interferon-gamma gene (IFNG) + 874 T/A polymorphism could be related to a predisposition to CD in the South American population [ 110 ] The single nucleotide polymorphism (SNP) rs6598045 of the interferon-induced transmembrane protein 3 (IFITM3) gene correlates with COVID-19 fatality rates [ 111 ] Populations with a low allele frequency of rs1990760 (T allele) in IFIH1 (InterFeron-Induced Helicase 1; MDA5) are associated with less IFN-beta expression and potential susceptibility to COVID-19 infection [ 112 ] ABO blood group system Inconclusive studies found an increase in blood group B patients dying suddenly from CD [ 113 ] The histo-blood group system explored by GTA, GTB, FUT II, and FUT III glycosyltransferases found that B plus AB secretor phenotypes are related to megaesophagus and megacolon in CD [ 114 ] GWAS found blood group A is associated with COVID-19 and respiratory failure [ 111 ] Type A blood is associated with the risk of in-hospital death [ 115 ] Ethnicity CD with megacolon, calibre and length of the rectosigmoid depends on altitude, ethnicity, and diet [ 116 ] COVID-19 presents an increased risk depending on the population studied, e.g. Black and Asian compared to white subjects had increased risk infection of COVID-19 [ 117 ] In Mexico, native peoples have a higher risk of death due to COVID-19 [ 118 ] Dysregulated immunothrombosis Hypercoagulability The activation of haemostasis is related to the activation and increase of various molecules, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The histo-blood group system explored by GTA, GTB, FUT II, and FUT III glycosyltransferases found that B plus AB secretor phenotypes are related to megaesophagus and megacolon in CD [ 114 ]…”
Section: Introductionmentioning
confidence: 99%